KEDUDUKAN MAJELIS KRAMA DESA DALAM MENYELESAIKAN SENGKETA BERDASARKAN PERATURAN BUPATI LOMBOK UTARA NOMOR 20 TAHUN 2017 TENTANG PEDOMAN MAJELIS KRAMA DESA (STUDI KASUS DI DESA GONDANG, KECAMATAN GANGGA, KABUPATEN LOMBOK UTARA) - ASMAYANDI ASMAYANDI; TITIN APRIANI; SYAIFULLAH SYAIFULLAH (GANEC SWARA, 2023)
The MKD institution was formed based on Regent Regulation Number 20 of 2017 concerning Guidelines for Village Krama Council. In Article 1 numbers 9 and 10 it is explained that: Village Community Institutions are institutions formed by the community according to needs and are partners of the village government in empowering village communities. The Krama Desa Council, hereinafter abbreviated as MKD, is a Village Community Institution in charge of dispute resolution in the Village. The formulation of the problem in this research is first, What is the Position of the Village Krama Council in Resolving Disputes Based on Regent Regulation Number 20 of 2017 concerning Guidelines for the Village Krama Assembly? And Second, how effective is the existence of the Village Krama Council in resolving disputes based on Regent Regulation Number 20 of 2017 concerning Guidelines for the Village Krama Council (Case Study in Gondang Village, Gangga District, North Lombok Regency)? The results of the research conducted by the author show that first, the Village Krama Council (MKD) was formed based on North Lombok Regent Regulation Number 20 of 2017 concerning Guidelines for the Village Krama Assembly (MKD) as a village government partner institution in resolving disputes that occur in village communities. The existence of the MKD institution in Gondang village was considered very effective because during the time the MKD was formed it had resolved various cases, ranging from civil, customary, and minor criminal cases, of which approximately 13 cases were recorded. However, in carrying out its functions, the MKD still has problems both internally and externally.